TELEVISION IN CHILE AS A CENTER FOR IDEOLOGICAL DISPUTES, FROM ITS ORIGINS UNTIL THE COUP D’État (1959-1973) - Secco, Lucía Jimena (Revista de Historia Social y de las Mentalidades, 2022)
This article searchs for inquiere in the processes that led to the growing politicization of television channels in Chile towards the end of the sixties and the beginning of the following decade. In this sense, not only the internal processes in universities and their relationship with national politics will be studied, but also the role of theoretical research linked to the mass media. It is understood here that the interrelation of the three factors (political system, generation of knowledge around the media and Chilean television system) resulted at the beginning of the seventies in a particular state of strong politicization in television, turning tv channels into political actors, where serveral interests were stressed.